SISTEM PAKAR PENANGANAN PENYAKIT KAMBING ETAWA MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract - The delay in knowing the type of disease and do not know how to prevent it resulted in a lot of goats, especially goats Etawa can not be saved. Therefore, with the advancement of computer technology has given its own influence to the development of Etawa goats. The influence that can be seen is in the form of equipment or systems. One is the Artificial Intelligence or commonly referred to as artificial intelligence. System development method used in this study is an expert system that consists of the identification, conceptualization, formalization, implementation and evaluation. Levelled system design using DFD diagram consisting of context and Level 0 DFD and ERD. Making a website using PHP and MySQL database. The end result of this research is the goat disease management expert system Etawa using forward chaining method can be used to solve the problem of handling Etawa goat disease because it can provide the diagnosis of any type of disease. Keywords – Expert System, Etawa, Forward Chaining